2018
DOI: 10.1111/1348-0421.12655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut microbiota composition between laboratory‐bred marmosets (Callithrix jacchus) with chronic diarrhea and healthy animals using terminal restriction fragment length polymorphism analysis

Abstract: Chronic diarrhea in laboratory-bred marmosets poses a serious health problem during experiments. Despite a growing demand for laboratory-bred experimental marmosets, the mechanisms underlying the development of diarrhea and measures for its treatment and prevention remain unclear. To explore the factors affecting development of chronic diarrhea in laboratory-bred marmosets, the gut microbiota composition (GMC) of 58 laboratory-bred marmosets, including 19 animals with chronic diarrhea, was analyzed using termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…We observed that at the genus level, Bifidobacterium was relatively abundant in both groups, which was consistent with the results of a previous study [15], partly due to the shared complete marmoset food in common with our colony. In the phylum Bacteroides, Group IF-specific changes were observed in the genus "Prevotella",, and only "Prevotella ruminicola" was identified in "Prevotella 1" in Table 2 at the species level.…”
Section: Impact On the Microbiomesupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that at the genus level, Bifidobacterium was relatively abundant in both groups, which was consistent with the results of a previous study [15], partly due to the shared complete marmoset food in common with our colony. In the phylum Bacteroides, Group IF-specific changes were observed in the genus "Prevotella",, and only "Prevotella ruminicola" was identified in "Prevotella 1" in Table 2 at the species level.…”
Section: Impact On the Microbiomesupporting
confidence: 92%
“…The numbers of lactobacilli were lower in the WMS group than in the non-WMS group, whereas those of Bacteroides-Fusobacteria and Clostridia were higher in the WMS group than in the non-WMS group. The group with a higher rate of chronic diarrhea had a lower proportion of Bifidobacterium than the other group, but there was no significant difference between the groups in terms of the Shannon diversity (H') index [15]. Because daily feeding regimens vary at each institute, the microbiome should vary accordingly; however, there are still insufficient data to characterize the gut microbiome distribution of captive common marmosets.…”
Section: Introductionmentioning
confidence: 99%
“…It may, therefore, provide insight into NHP risk of GI distress in captive environments. A few studies have explored links between GI disease and gut microbiome composition in captive NHPs (Amato et al, ; McKenna et al, ; Shigeno et al, ). These studies suggest that changes in the relative abundances of some microbial taxa may both increase susceptibility to GI disease and trigger its emergence.…”
Section: Introductionmentioning
confidence: 99%
“…in the CFMA, eight belonged to the family Enterobacteriaceae. Some species of bacteria of this family are considered commensal for both humans and animals, such as E. coli, K. pneumoniae and Proteus mirabilis, but can lead to opportunistic infections; however, other species such as Salmonella enterica can cause serious gastroenteritis (Bublitz et al, 2015;Shigeno et al, 2018;Zaniolo et al, 2018). Results of the present study showed that K. pneumoniae was the most frequent bacterium in the rectum (85.7%) and the second most frequent in the oral cavity (28.6%) of the marmosets assessed.…”
Section: Discussionmentioning
confidence: 99%
“…and Listeria sp. (Burke et al, 2009;Carvalho et al, 2014;Sales, 2015;Cruz et al, 2017;Shigeno et al, 2018;Takehara et al, 2019). In humans, these bacteria may constitute important opportunistic pathogens that promote severe conditions of urinary tract infection, gastroenteritis, liver abscesses, and septicemia (Carrier et al, 2009;Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%